The cognitive neuroscience of crossmodal correspondences. - Spence, C; Parise, C (2012)
In a recent article, N. Bien, S. ten Oever, R. Goebel, and A. T. Sack (2012) used event-related potentials to investigate the consequences of crossmodal correspondences (the "natural" mapping of features, or dimensions, of experience across sensory modalities) on the time course of neural information processing. Then, by selectively lesioning the right intraparietal cortex using transcranial magnetic stimulation, these researchers went on to demonstrate (for the first time) that it is possible to temporarily eliminate the effect of crossmodal congruency on multisensory integration (specifically on the spatial ventriloquism effect). These results are especially exciting given the possibility that the cognitive neuroscience methodology utilized by Bien et al. (2012) holds for dissociating between putatively different kinds of crossmodal correspondence in future research.